G gamma delta beta thalassaemia and g gamma HPFH (Hb Kenya type): comparison of 2 new cases. - Wood, W G (1977)
Two new cases of G gamma delta beta thalassaemia and G gamma HPFH (Hb Kenya type) have been characterised in detail and compared with regard to haematological data, globin chains biosynthesis, and intracellular distribution of Hb F. The similarities and differences between these two conditions are discussed in relation to the possible underlying defects at the molecular level and to the control of the gamma delta beta gene complex in general.